The population genomic analyses of chloroplast genomes shed new insights on the complicated ploidy and evolutionary history in Fragaria - Song, Yanhong; Li, Chaochao; Liu, Lifeng; Hu, Panpan; Li, Gang; Zhao, Xia; Zhou, Houcheng (Frontiers in Plant Science, 2023)
The genus Fragaria consists of a rich diversity of ploidy levels with diploid (2x), tetraploid (4x), pentaploid (5x), hexaploidy (6x), octoploid (8x) and decaploid (10x) species. Only a few studies have explored the origin of diploid and octoploid strawberry, and little is known about the roles of tetraploidy and hexaploidy during the evolution of octoploid strawberry. The chloroplast genome is usually a stable circular genome and is widely used in investigating the evolution and matrilineal identification. Here, we assembled the chloroplast genomes of F. x ananassa cv. ‘Benihoppe’ (8x) using Illumina and HiFi data seperately. The genome alignment results showed that more InDels were located in the chloroplast genomes based on the PacBio HiFi data than Illumina data. We obtain highly accurate chloroplast genomes assembled through GetOrganelle using Illumina reads. We assembled 200 chloroplast genomes including 198 Fragaria (21 species) and 2 Potentilla samples. Analyses of sequence variation, phylogenetic and PCA analyses showed that Fragaria was divided into five groups. F. iinumae, F. nilgerrensis and all octoploid accessions formed Group A, C and E separately. Species native to western China were clustered into Group B. Group D consisted of F. virdis, F. orientalis, F. moschata, and F. vesca. STRUCTURE and haplotype network confirmed that the diploid F. vesca subsp. bracteata was the last maternal donator of octoploid strawberry. The dN/dS ratio estimated for the protein-coding genes revealed that genes involved in ATP synthase and photosystem function were under positive selection. These findings demonstrate the phylogeny of totally 21 Fragaria species and the origin of octoploid species. F. vesca was the last female donator of octoploid, which confirms the hypothesis that the hexaploid species F. moschata may be an evolutionary intermediate between the diploids and wild octoploid species.